Orson Welles in focus : texts and contexts - Gilmore, James, 1989-; Gottlieb, Sidney (Indiana University Press, 2018)
Through his radio and film works, such as The War of the Worlds and Citizen Kane, Orson Welles became a household name in the United States. Yet Welles's multifaceted career went beyond these classic titles and included lesser-known but nonetheless important contributions to television, theater, newspaper columns, and political activism. Orson Welles in Focus: Texts and Contexts examines neglected areas of Welles's work, shedding light on aspects of his art that have been eclipsed by a narrow focus on his films. By positioning Welles's work during a critical period of his activity (the mid-1930s through the 1950s) in its larger cultural, political, aesthetic, and industrial contexts, the contributors to this volume examine how he participated in and helped to shape modern media. This exploration of Welles in his totality illuminates and expands our perception of his contributions that continue to resonate today.